Effectiveness of Using Drops Application in English Vocabulary on Students’ Learning Outcomes - Sabilla, Sonia; Sholihatul Hamidah Daulay (Universitas Muhammadiyah Jember, 2025)
The study aims to determine the effect of using an English vocabulary learning application called